The Impact of Employee Job Satisfaction and Lack of Job Alternatives toward Employee Retention of Generation Y in Indonesia - Karen Christabel; Paulivia Dewi Sutanto (iBuss Management, 2018)
This research is used to determine the factors that are influencing employee job satisfaction of Generation Y in Indonesia. In addition, this research is also used to test whether both employee job satisfaction and lack of job alternatives are influencing employee retention of Generation Y in Indonesia.This research uses quantitative method with multiple linear regression as the statistical method for the analysis. This research shows that the factor of Spector’s (1997) job satisfaction is influencing the employee job satisfaction of Generation Y in Indonesia simultaneously, but not individually. Individually, only nature of work and communication are the two factors that are influencing employee job satisfaction. The other result of this research is both employee job satisfaction and lack of job alternatives are impacting the employee retention of Generation Y in Indonesia in both simultaneously and individually. Keywords: Generation Y, Employee Job Satisfaction, Lack of Job Alternatives, Employee Retention.